The Correlation Between Students’ Visual Learning Style Preference and Vocabulary Mastery at SMP NEGERI 3 Sungguminasa - Fakhirah, Ferra; Latief, Hasnawati; Arief Muhsin, Muh (FKIP Unismuh Makassar, 2023)
The objective of this research is to find out the correlation between students' visual learning style preference and vocabulary mastery at SMP Negeri 3 Sungguminasa. The design of this research is descriptive quantitative research. This research has two variables, students' visual learning style preference as an independent variable and students’ vocabulary mastery as a dependent variable. The population of this research is seventh-grade students. The researcher used random sampling to take the samples, which consist of 33 students. In collecting the data, the researcher used a questionnaire and test. The questionnaire used to measure students’ visual learning style preference, which consists of 15 statements. Then, the test is used to know students’ vocabulary mastery which consists of 20 questions. In analyzing the data, the researcher used Pearson analyzed Product Moment Correlation formula. The data analyzed by using SPSS 23 program for Windows. The result of this research shows that there was a medium correlation between students’ visual learning style preference and vocabulary mastery of VII grade students of SMP Negeri 3 Sungguminasa because the value of rxy = 0.468 on the correlation scale table (0.40-0.599) means in medium correlation level. As the findings showed, rxy > rtable = 0.468 >0.40 So, it can be concluded that there was a significant correlation between students’ visual learning style and vocabulary mastery at SMP Negerei 3 Sungguminasa